INFESTAÇÃO DE COLEOBROCAS EM MADEIRAS DE Eucalyptus spp. EM CUIABÃ, ESTADO DE MATO GROSSO - Dorval, Alberto; Peres Filho, Otávio; Marques, Eli Nunes; Berti Filho, Evoneo; Moura, Rogério Goularte (REVISTA DE AGRICULTURA, 2015)
INFESTAÇÃO DE COLEOBROCAS EM MADEIRAS DE Eucalyptus spp. EM CUIABÃ, ESTADO DE MATO GROSSO